Teenage pregnancy : the making and unmaking of a problem - Arai, Lisa (Health and society series., 2009)
This title provides an introduction to teenage pregnancy. It examines who is likely to have a baby as a teenager, the consequences of early motherhood and how teenage pregnancy is dealt with in the media.